Regioselective formation of saturated abnormal NHC-Gold(I) complexes by [3+2] cycloaddition of azomethine ylides and isonitrile gold(I) complexes - Hashmi, A. Stephen K.; Riedel, Dominic; Rudolph, Matthias; Rominger, Frank; Oeser, Thomas (Chemistry - a European journal, 2012)
Abnormally easy: The first saturated abnormal NHC-gold(I) complexes are synthesized in a two-step procedure from commercially available gold(I) precursors. The reaction of gold-coordinated isonitriles with in situ generated azomethine ylides circumvents regioselectivity problems during the carbene formation (see scheme). The scope of the reaction turned out to be general and abnormal carbenes with unusual substitution patterns are thus accessible.
Gesehen am 06.09.2018